Synthesis and characterization of SBA-15 modified with alkali metals - Cano, L. A. (2016)
A synthesis protocol that has not been previously reported in the literature that allows doping a solid of SBA-15 with alkali metals, preserving the structural features of the mesoporous solid has been developed. X-ray diffraction at low angles, Nitrogen adsorption, Electron transmission microscopy, X-ray photoelectron spectra, atomic absorption spectroscopy and Thermal Programmed Desorption of carbon dioxide were used to characterize the solids obtained. The introduction of alkali metals within the channels of the solid generates basic sites of weak and intermediate strength, which do not exist in undoped SBA-15. Without significant changes in the structural and textural properties of the support, only the densification of the channel walls is evidenced. According to the alkali metal used, the order established by the total number of sites obtained is: Li-SBA-15 ≫ K-SBA-15 ≈ Cs-SBA-15, while the order by force of both types of sites (weak and intermediate) is: Li-SBA-15 > Cs-SBA-15 > K-SBA-15.